PERAN KEPUASAN KERJA DALAM MEMEDIASI PENGARUH WORK-LIFE BALANCE TERHADAP KINERJA PEGAWAI PADA RUMAH DETENSI IMIGRASI DENPASAR - Putri, Anak Agung Istri Cahyani; Mujiati, Ni Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.04.TAHUN.2023DO - 10.24843/EEB.2023.v12.i04.p13, 2023)
This study aims to determine the role of job satisfaction in mediating the effect of work-life balance on employee performance at the Denpasar immigration detention house. The population in this study were all employees at the Immigration Detention Center as many as 60 people. The number of samples used in this study were 60 respondents using a saturated sampling technique, where all members of the population were used as research samples. Methods of data collection using interviews and questionnaires. With data analysis techniques, namelypath analysis, Sobel test and testing the role of mediation. The results showed that work-life balance has a positive and significant effect on employee performance, work-life balance has a positive and significant effect on job satisfaction, job satisfaction has a positive and significant effect on employee performance and job satisfaction is a mediating variable for the effect of work-life balance on employee performance. The theoretical implications of the results of this study provide evidence on the development of human resource management science, especially regarding work-life balance, job satisfaction and employee performance which is able to empirically prove the theory used in this study, namely attribution theory.